2009
DOI: 10.1007/s11069-009-9487-8
|View full text |Cite
|
Sign up to set email alerts
|

Submarine landslides at the eastern Sunda margin: observations and tsunami impact assessment

Abstract: Our analysis of new bathymetric data reveals six submarine landslides at the eastern Sunda margin between central Java and Sumba Island, Indonesia. Their volumes range between 1 km³ in the Java fore-arc basin up to 20 km³ at the trench off Sumba and Sumbawa. We estimate the potential hazard of each event by modeling the corresponding tsunami and its run-up on nearby coasts. Four slides are situated remarkably close to the epicenter of the 1977 tsunamigenic Sumba M w =8.3 earthquake. However, comparison of docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…The largest slides of our study (sites 9, 11, and 12 with a volume of 15 to 20 km 3 ) were found 150 km southeast of Sumba and 250 km south of Sumbawa (in Brune et al, 2009b, they are denominated C, E, and F, respectively). They generated large tsunamis with maximum run-up heights of nearly 6 m on Sumbawa for slides 9 and 11.…”
Section: Landslides In New Bathymetry Data and Tsunami Calculationsmentioning
confidence: 61%
See 3 more Smart Citations
“…The largest slides of our study (sites 9, 11, and 12 with a volume of 15 to 20 km 3 ) were found 150 km southeast of Sumba and 250 km south of Sumbawa (in Brune et al, 2009b, they are denominated C, E, and F, respectively). They generated large tsunamis with maximum run-up heights of nearly 6 m on Sumbawa for slides 9 and 11.…”
Section: Landslides In New Bathymetry Data and Tsunami Calculationsmentioning
confidence: 61%
“…We studied whether the slope failures generated a tsunami and how much run-up was generated at the shore using numerical tsunami modeling for the events at site 4 (Brune et al, 2009a) and 7 to 12 (Brune et al, 2009b). We thereby applied the nonlinear shallow water code TUNAMI-N2 (Imamura et al, 1997) to calculate wave propagation from the slide to the shore.…”
Section: Landslides In New Bathymetry Data and Tsunami Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic amplitude accuracy regarding the equation is ±5.3%. The results show that the observed landslide would have generated a tsunami wave of about 4450 m wave length and with a maximum wave height of about 0.12 m. These initial wave characteristics could be input criteria for tsunami propagation models (Synolakis et al, 2002;Brune et al, 2009) in order to calculate wave propagation and potential onshore run-up. However, the small initial wave height already indicates that the observed submarine landslide could not generate a devastating tsunami on the coast.…”
Section: Discussionmentioning
confidence: 98%